2020 AHA/ACC Guideline for the Diagnosis and Treatment of Patients With Hypertrophic Cardiomyopathy: A Report of the American College of Cardiology/American Heart Association Joint Committee on Clinical Practice Guidelines. Issue 25 (22nd December 2020) - Ommen, Steve R.; Mital, Seema; Burke, Michael A.; Day, Sharlene M.; Deswal, Anita; Elliott, Perry; Evanovich, Lauren L.; Hung, Judy; Joglar, José A.; Kantor, Paul; Kimmelstiel, Carey; Kittleson, Michelle; et al.
Abstract : Supplemental Digital Content is available in the text.